2008
DOI: 10.1108/13590790810866854
|View full text |Cite
|
Sign up to set email alerts
|

The role of private sector organizations in the control and policing of serious financial crime and abuse

Abstract: Purpose -While the "Information Age" has provided the technological tools to "democratize" data and make it widely available to a vast audience of knowledge consumers, ironically it has also provided the materials for a tapestry of rules, regulations and processes that make it more difficult for individuals to access information relevant to both their public and private lives. The purpose of this paper is to examine the role of the private sector in the control and policing of financial crime, and provide an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…For example, a disincentive can be found in customers who demand secrecy in their financial dealings. Gilsinan et al (2008) argue further that the temptation towards malfeasance is high when the private sector is responsible for both the provision and production of industry regulation. Behaviours change when such provision and production is linked to fraudulent activity perpetrated by individuals external to the organization and when either government resources or likelihood of success are in short supply.…”
Section: Officer-to-officer Stagementioning
confidence: 96%
See 1 more Smart Citation
“…For example, a disincentive can be found in customers who demand secrecy in their financial dealings. Gilsinan et al (2008) argue further that the temptation towards malfeasance is high when the private sector is responsible for both the provision and production of industry regulation. Behaviours change when such provision and production is linked to fraudulent activity perpetrated by individuals external to the organization and when either government resources or likelihood of success are in short supply.…”
Section: Officer-to-officer Stagementioning
confidence: 96%
“…Gilsinan et al (2008) argue that a calculus of incentives and disincentives determines to what extent the role of informant is adopted by the private sector. For example, a disincentive can be found in customers who demand secrecy in their financial dealings.…”
Section: Officer-to-officer Stagementioning
confidence: 99%
“…For the investigator friendly, an incentive is external business threats from fraudulent activity by competitors. Gilsinan et al (2008) argue further that the temptation towards malfeasance is high when the private sector is responsible for both the provision and production of industry regulation. Behaviours change when such provision and production is linked to fraudulent activity perpetrated by individuals external to the organization and when either government resources or likelihood of success are in short supply.…”
Section: Stage Iii: Investigator-to-informationmentioning
confidence: 96%
“…Gilsinan et al (2008) identified this contribution in terms of five distinct roles. Each role has its own dynamics and implications for successful suppression of unlawful conduct.…”
Section: Stage Iii: Investigator-to-informationmentioning
confidence: 97%
See 1 more Smart Citation